2015
DOI: 10.1002/2015gl066219
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-dependent isotope fractionation in visible light O3 photolysis and atmospheric implications

Abstract: The 17O and 18O isotope fractionation associated with photolysis of O3 in the Chappuis band was determined using a broadband light source with cutoff filters at 455, 550, and 620 nm and narrowband light sources at 530, 617, and 660 nm. The isotope effects follow a mass‐dependent fractionation pattern (δ17O/δ18O = 0.53). Contrary to theoretical predictions, fractionations are negative for all wavelength ranges investigated and do not change signs at the absorption cross‐section maximum. Our measurements differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Initial evidence for this comes from laboratory experiments (Bhattacharya and Thiemens, 1988;Chakraborty and Bhattacharya, 2003), and was recently substantiated by measurements where photolytic O 3 removal could be analytically separated from chemical removal (Früchtl et al, 2015a). Wavelengthdependent isotope effects in O 3 photolysis are also suggested by theoretical calculations (Miller et al, 2005;Liang et al, 2006;Ndengué et al, 2014), but the agreement of these calculations with new high-precision measurements is relatively poor (Früchtl et al, 2015b). Nevertheless, isotope effects in photolysis have been suggested as an explanation for the high enrichments found by balloon measurements in the upper stratosphere (Haverd et al, 2005;Krankowsky et al, 2007), where the effects of the formation reaction fall short of the observed enrichments by 2-4 %.…”
Section: Introductionmentioning
confidence: 99%
“…Initial evidence for this comes from laboratory experiments (Bhattacharya and Thiemens, 1988;Chakraborty and Bhattacharya, 2003), and was recently substantiated by measurements where photolytic O 3 removal could be analytically separated from chemical removal (Früchtl et al, 2015a). Wavelengthdependent isotope effects in O 3 photolysis are also suggested by theoretical calculations (Miller et al, 2005;Liang et al, 2006;Ndengué et al, 2014), but the agreement of these calculations with new high-precision measurements is relatively poor (Früchtl et al, 2015b). Nevertheless, isotope effects in photolysis have been suggested as an explanation for the high enrichments found by balloon measurements in the upper stratosphere (Haverd et al, 2005;Krankowsky et al, 2007), where the effects of the formation reaction fall short of the observed enrichments by 2-4 %.…”
Section: Introductionmentioning
confidence: 99%
“…These issues are important in determining the atmospheric ozone isotope composition and as input to the ozone isotope transfer models. A recent study by Früchtl et al () in visible light photolysis was done using two wavelength ranges: (i) over a broad range of 455 to 800 nm giving average values of isotopic fractionation ranging from −15.2‰ to −26.9‰ and (ii) in three narrow band wavelengths of 530, 617, and 660 nm which gave values of −12.9‰, −15.0‰, and −23.9‰, respectively. These results are also in conflict with the model predictions for the visible light, both in magnitude and directions.…”
Section: Motivationmentioning
confidence: 99%
“…In the stratosphere, the dominant processes controlling the isotopic composition of ozone are two: formation and photolysis. The isotopic effects due to the former have been well established (Brenninkmeijer et al, ; Gao & Marcus, ; Janssen et al, , ; Mauersberger et al, ; Morton et al, ; Thiemens, ; Thiemens & Heidenreich, ), but understanding the changes due to photolysis is still unsatisfactory (Bhattacharya & Thiemens, ; Chakraborty & Bhattacharya, ; Früchtl et al, ; Wen & Thiemens, ). The reason is that photolysis of ozone in laboratory is always associated with two secondary interfering processes: formation of fresh ozone and ozone dissociation through reactive atomic and molecular oxygen species, which are formed due to the photolysis itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial evidence for this comes from laboratory experiments (Bhattacharya and Thiemens, 1988;Chakraborty and Bhattacharya, 2003), and was recently substantiated by measurements where photolytic O 3 removal could be analytically separated from chemical removal (Früchtl et al, 2015a). Wavelengthdependent isotope effects in O 3 photolysis are also suggested by theoretical calculations (Miller et al, 2005;Liang et al, 2006;Ndengué et al, 2014), but the agreement of these calculations with new high-precision measurements is relatively poor (Früchtl et al, 2015b). Nevertheless, isotope effects in photolysis have been suggested as an explanation for the high enrichments found by balloon measurements in the upper stratosphere (Haverd et al, 2005;Krankowsky et al, 2007), where the effects of the formation reaction fall short of the observed enrichments by 2-4 %.…”
Section: Introductionmentioning
confidence: 99%